PENGARUH DANA ALOKASI UMUM, DANA ALOKASI KHUSUS, DAN DANA BAGI HASIL TERHADAP INDEKS PEMBANGUNAN MANUSIA PADA KAB./KOTA PROPINSI SUMATERA UTARA - RIVA UBAR HARAHAP (Jurnal Riset AKuntansi dan Bisnis, 2011)
The  purpose  of  this  study  is  to  identify  and  analyze  whether  General Allocation Fund (DAU), Special Allocation Fund (DAK) and Profit Sharing Fund (DBH) influence simultaneously and partially to Human Development Index (IPM). The analytical method used  is  multiple  regressions  by  doing  classic assumption test method prior to gather the best model research.  These variabel research such as the General Allocation Fund, Special Allocation Fund and Profit Sharing  Fund  are  independent  variables  and  Human  Development  Index  is dependent variable. Research sample is 25 district/city in North Sumatera Province. DAU, DAK and DBH obtained from www.djpkd.depkeu.go.id. The data of Human Development Index obtained from Indonesia Statistics Centre Institution.  The results of this study concluded that the General Allocation Fund, Special Allocation Fund and Profit Sharing Fund influence simultaneously to the Human Development Index. The result consistent  with  research  hypothesis. General Allocation Fund, Special Allocation Fund and Profit Sharing Fund have no effect partially to the Human Development Index. The result consistent with research hypothesis.